ENVIRONMENTAL KUZNETS CURVE: THE CASE OF CANADA, SPAIN AND INDONESIAN ON CO2EMISSION - Erwinsyah (MBA - Journal of Management and Business Aplication, 2021)
The Environmental Kuznets Curve is used to investigate the relationship between various indicators of environmental degradation and income per capita. The economic growth measured from the change of income per capita contributes negative externalities to nature, and education contributes to better knowledge for sustainable development. The purpose of this research was to apply the Environmental Kuznets Curve to see the impact of income per capita and education on environmental degradation. The objective of this research was to examine how GDP per capita and education contribute to per capita CO2emission in Canada, Spain, and Indonesia. The research output showed a relationship between per capita GDP with per capita CO2emission in Canada and Spain. Contribution of per capita GDP to per capita CO2emission of Canada higher than Spain. The higher per capita GDP will rise per capita CO2emission. The per capita GDP of Indonesia does did contribute significantly to per capita CO2emission. The was also a significant relationship between education quality and per capita CO2emission in Canada, Spain, and Indonesia. The better education quality in Canada and Spain contribute to lower per capita CO2 emissions. Education quality in Indonesia contributed to the higher per capita CO2emission. Keywords:Environmental Kuznets Curve, Per Capita CO2 Emission, Per Capita GDP, Education